Predicting Teacher Engagement through Culturally Responsive Teaching: A Mixed-Methods Study in the Marrakech ELT Context - Kettani, Moulay Tahar; Ouahidi, Lalla Meriem (International Journal of Language and Literary Studies, 2026)
Researchers in this study conducted a linear regression analysis to discover the predictive relationship between culturally responsive teaching (CRT) and teacher engagement (TE) among English as a Foreign Language (EFL) teachers in the Marrakech directorate, Morocco. This study used an exploratory sequential mixed-methods design, in which the researchers first conducted in-depth interviews with 12 EFL teachers to develop CRT and TE scales that were culturally relevant to the context. The researchers then used these scales to collect quantitative data from a sample of 105 secondary school EFL teachers. The research shows a positive, statistically significant correlation between CRT and TE, and linear regression results indicate that CRT explains approximately 10% of the variance in TE, suggesting that implementing culturally responsive teaching practices is indeed associated with students' learning experiences and higher teacher engagement. Researchers believe that to maximize the potential of teacher engagement and professional satisfaction, CRT principles must be embedded in both pre-service and in-service professional development. The study also offers policy implications and recommendations for future research in multicultural English Language Teaching. <!--a=1-->